2017
DOI: 10.1038/srep45842
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of tetragonal anisotropy and stabilisation of the tetragonal phase by Bi/Mn-double-doping in BaTiO3 ferroelectric ceramics

Abstract: To stabilise ferroelectric-tetragonal phase of BaTiO3, the double-doping of Bi and Mn up to 0.5 mol% was studied. Upon increasing the Bi content in BaTiO3:Mn:Bi, the tetragonal crystal-lattice-constants a and c shrank and elongated, respectively, resulting in an enhancement of tetragonal anisotropy, and the temperature-range of the ferroelectric tetragonal phase expanded. X-ray absorption fine structure measurements confirmed that Bi and Mn were located at the A(Ba)-site and B(Ti)-site, respectively, and Bi wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 53 publications
(53 reference statements)
2
7
0
Order By: Relevance
“…In order to calculate the magnetic moment per Mn ion and considering a high‐spin state, the Curie constant has been evaluated. The S quantum number is 5/2, 2, and 3/2 for the valence states of Mn 2+ , Mn 3+ , and Mn 4+ , respectively, in agreement with the fact that Mn ions doping the tetragonal phase acquire the Mn3+ valence state, thus the selected value for the S quantum number is 2. The Curie constant depends on the ion concentration and can be expressed as follows:Cfalse(xfalse)=xnormalC0=xN(gnormalμnormalB)2Sfalse(normalS+1false)/3knormalBwhere g is the Landé g ‐factor, x = 1 is the atomic Mn concentration, N is the number of ions per unit volume, μ B the Bohr magneton, and k B is the Boltzmann constant.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…In order to calculate the magnetic moment per Mn ion and considering a high‐spin state, the Curie constant has been evaluated. The S quantum number is 5/2, 2, and 3/2 for the valence states of Mn 2+ , Mn 3+ , and Mn 4+ , respectively, in agreement with the fact that Mn ions doping the tetragonal phase acquire the Mn3+ valence state, thus the selected value for the S quantum number is 2. The Curie constant depends on the ion concentration and can be expressed as follows:Cfalse(xfalse)=xnormalC0=xN(gnormalμnormalB)2Sfalse(normalS+1false)/3knormalBwhere g is the Landé g ‐factor, x = 1 is the atomic Mn concentration, N is the number of ions per unit volume, μ B the Bohr magneton, and k B is the Boltzmann constant.…”
Section: Resultssupporting
confidence: 70%
“…The Curie constant in our system (the inverse of the value of the slope of the straight line in the inset of Figure B) is C = 0.0182 emu K/Oe cm 3 . A recent report of bulk BaTiO 3 ceramics with a Mn concentration of 0.3% leads to C = 0.004858 emu K/Oe cm 3 . Additional values obtained in diluted systems with paramagnetic behavior are C = 0.04021 emu K/Oe cm 3 in Zn 0.95 Mn 0.5 O and C = 0.0201 emu K/Oe cm 3 in Zn 0.95 Co 0.5 O for sol‐gel prepared bulk samples; C = 0.01633 emu K/Oe cm 3 in In 2 SnO 5 :Mn at a 5 at.% thin films, and C = 0.0316 emu K/Oe cm 3 in Co 0.5 (Mg 0.55 Zn 0.45 ) 0.5 O 1− ν epitaxial thin films .…”
Section: Resultsmentioning
confidence: 95%
“…A decrease of oxygen vacancy content leads to an increase in the sample tetragonality ( c/a ), and thus, the observed ferroelectric polarization value. , On the other hand, increased substitution of a larger Ba ion by a relatively smaller Bi ion in tetragonal BTO phase adversely impacts the ferroelectric mode i.e. the Ti off-centric distortion, and along with it the sample tetragonality. Thus, an interplay of these two counter forces (i.e., the reduction of oxygen-vacancy favoring the tetragonality and the substitution of Ba by smaller Bi ion opposing the tetragonality) is at work with increasing Bi doping in the BBTFO series, and as a result, the tetragonality of the unit cell first increases until x = 0.02 and, thereby, continues to decrease with further increase in x .…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, environmental (extrinsic) factors also play a role in the kinetics of the dissolution. Furthermore, while it has been shown that doping sometimes stabilize crystal structures [ 134 ], in general it induces instability that leads to higher dissolution and leaching of ions [ 135 ] that may be toxic [ 136 ]. NMs doping alters the band gap of the material compared to pristine NMs [ 122 ], which has been linked to oxidative stress in biological organisms when it overlaps with the redox potential for biological reactions [ 69 , 137 ].…”
Section: Resultsmentioning
confidence: 99%